If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3sinx + cosx = 2 Reorder the terms: cosx + 3insx = 2 Solving cosx + 3insx = 2 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3insx' to each side of the equation. cosx + 3insx + -3insx = 2 + -3insx Combine like terms: 3insx + -3insx = 0 cosx + 0 = 2 + -3insx cosx = 2 + -3insx Divide each side by 'osx'. c = 2o-1s-1x-1 + -3ino-1 Simplifying c = 2o-1s-1x-1 + -3ino-1 Reorder the terms: c = -3ino-1 + 2o-1s-1x-1
| 12-9x=23-16x | | 57.99+.11x=58.54 | | (5b-3)(2b-6)-(-3+8b)(4b-4)= | | .23x+2.34=6.25 | | 4f-12=16 | | 4x^2-9x+9=7x+2 | | =2+3 | | 112-2x=6x+16 | | 2f+g=13 | | a+4b=18 | | 24-t=18 | | h-14=23 | | 20-1.45=1.15 | | 3(2+x)=10+x | | 4x=3+3x | | x-2-8=3 | | 6v=24 | | t+26=41 | | (x^5+y^2)(x^5-Y^2)= | | 0=8+2y | | 2(123*34)= | | 110=80+2xwidth | | 4x^2-3x+16=0 | | -4.3-.1x=-6.1 | | (5a-1)(6a-3)= | | -15+5x=11+3x | | 0=2x+10 | | -5+5x=11+3x | | 0=x+5 | | 0=x-1 | | -2+3x=14+5x | | 8-1=63 |